G507 Complex care attending model. (25th October 2020) - Roberts, S; Ramachandran, R; Gough, J; Wicks, C; Butler, M; Cheung, R; Tiesman, B; Cockar, I
Abstract : Aim: Our current working paediatric model is based around a rapid turnover of acutely unwell children with none or limited co-morbidities, who are expected to return to prior health with appropriate medical management. In order to fulfil these standards we operate a weekly attending consultant system with resident on calls until 9pm, with a focus on acutely unwell children including fulfilling standard of consultant review of acute admission within 14 hours of admission. We have increasingly realised that this model of care in insufficient to care effectively for patients with more complex medical and social health needs. We are to piloting a new model of care to improve the care of Children with Complex Medical needs. This involves a second Ward Attending Consultant to focus on their care, supported by a new administrative role and Clinical nurse specialist (CNS) role. Method: The Second Attending Consultant of the week, instead of managing acute medical admissions focusses on these children and families supported by an administrator and the Complex CNS. The model moves away from the daily ward rounds needed by acute patients, with instead twice weekly reviews and a greater focus on coordinating effective Multidisciplinary meetings, addressing psychosocial needs and good communication with families. The changes are based on Qualitative feedback from Staff and Family. Regular evaluation of the effectiveness of the service change has been started alongside a narrative of barriers to change and complications to help inform next steps. Results: Monthly data is collected as indirect measures of improved communication between professionals and has improved from as baseline; time to first Multidisciplinary meeting, time Community teams informed of admission and discharge. Quantitative data regarding length of stay, A&E attendance, hospital admissions and missed Community appointments due to inpatient stay has been collected as a baseline. Early data shows a reduction in length of stay, data collection for other parameters are planned in January 2020 alongside repeat staff and patient surveys. Conclusion: The paediatric complex care second attending model has enabled improved communication and reduced length of stay for patients with complex medical and social needs